Statistical Temporal Variations in the Auroral Electrojet Estimated With Ground Magnetometers in Fennoscandia - Simon Walker; Karl Laundal; Jone Reistad; Anders Ohma; Spencer Hatch (Space Weather)
Abstract We present the implementation of an improved technique to coherently model the high‐latitude ionospheric equivalent current. Using a fixed selection of 20 ground magnetometers in Fennoscandia, we present a method based on Spherical Elementary Current Systems (SECS) to model the currents coherently during 2000–2020. Due to the north‐south extent of the magnetometers, we focus on the model output along the 105° magnetic meridian. Our improvements involve fixed data locations and SECS analysis grid and using a priori knowledge of the large‐scale currents improving the robustness of the inverse problem solution. We account for contributions from ground induced currents assuming so‐called mirror currents. This study produces a new data set of divergence‐free (DF) currents and magnetic field perturbations along the 105° magnetic meridian with 1‐min resolution. By comparing averages of the data set with an empirical model of the ionosphere we demonstrate the validity of the data set. We show how our data set, in particular its temporal nature, is distinct from empirical models and other studies. Not only can the temporal evolution of the DF currents and magnetic field perturbations be investigated, but the time derivative of said quantities can be analyzed. For application in ground induced currents, we present the statistical properties of where (in magnetic latitude and local time) and at what rate (∂Br/∂t) the radial magnetic field component fluctuates, a temporal derivative that has received very little attention. We show that ∂Br/∂t is dependent on latitude, local time, and solar cycle. We present other applications such as Ultra Low Frequency Waves monitoring.